PERANCANGAN, PEMBUATAN DAN PENGUJIAN MODEL AEROELASTIS PENAMPANG JEMBATAN BENTANG PANJANG - Sangadji, Senot
Abstract: In the wind-structure interaction, long span cable supported bridge have problems which is called aeroelastic phenomena. One of the solution of these problem is experimental studies. Experiment was carried out in this thesis to determine coefficients of lift, drag and aerodynamic moment and to determine the dynamic stability boundary of bridge section. Research was carried out by designing 2 D typical section of the bridge which is a result of Sunda strait feasibility study. Model is developed for 4 fairing variation. The physical model is made from glass fiber as a principal material. Flowfield dynamic similarity and structural dynamic character similarity is maintain trough nondimensional number. Determination of aerodynamic coefficients was carried out using balance method whereas aodynamic forces is measured by strain gages balance. Flutter margin is determined using Zimmerman method which is derived from Routh-Hurwitz dynamic stability criterion. Results show degree of stability sensitifity for sectional shape variation, represented by critical flutter speed.